Gamma knife radiosurgery for cavernous sinus plasmacytoma in a patient with breast cancer history - BAYRAKLI, FATİH (ELSEVIER SCIENCE INC, 2005)
Background: Multiple myeloma (MM) presentation with cerebral mass lesion is unusual. Gamma knife radiosurgery for plasmacytoma has not been reported so far. Case Report: We report a 70-year-old female with a medical history of infiltrative ductal carcinoma of the breast. She developed cavernous sinus syndrome (CSS) 5 months before admission to the hospital. The magnetic resonance imaging revealed an isointense solitary mass in the left cavernous sinus in noncontrast T1-weighted images. The lesion was highly enhancing with gadolinium-diethylenetriaminopentaacetic acid. She was operated by using Dolenc technique, and the tumor was partially resected. The pathological examination of the tumor tissue revealed a plasmacytoma. Systemic evaluation was positive for the diagnosis of MM. She underwent gamma knife radiosurgery for the residual cavernous sinus tumor. Chemotherapy with prednisolone and melphalan was given. Follow-up magnetic resonance images 6 months after the treatment demonstrated complete tumor disappearance. However, she died of sepsis 26 months after the diagnosis. Conclusion: This is an unusual MM case with a history of breast cancer, which had CSS and which demonstrated an excellent response to gamma knife radiosurgery. (C) 2005 Elsevier Inc. All rights reserved.
Keywords: breast cancer; multiple myeloma; plasmacytoma; radiosurgery; second malignancy; MULTIPLE-MYELOMA; CONSERVATIVE SURGERY; RADIATION